The matter of attitude in second The matter of attitude in second language learning.: The matter of attitude in second language learning. - Majidova, Gulruh (Maktabgacha taʼlim jurnali, 2022)
Abstract: There are different factors that influence on learning foreign langugaes. Learner’s attitude and perception are two of the most important ones which can be stimulator in learning the target language. These concepts are the focal points of sociolinguists as far as learners’ behavior is concerned. Therefore, the article discusses the role of attitude and perception and their impacts on learners’ learning abilities.